ISOLATION, IDENTIFICATION AND ANTIMICROBIAL SUSCEPTIBILITY OF BRUCELLA BLOOD CULTURE ISOLATES - Cekovska, Z; Petrovska, M; Jankoska G; Panovski, N; Kaftandzieva, A (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2010)
Isolation of slowly growing and fastidious Brucella spp strains from clinical specimens is difficult, because of varying factors, including species specificities, stadium of disease, and previous antibiotic treatment of the patients. The use of automated blood culture systems has overcome some cultivation problems. The automated identification system such as VITEK 2 compact allows more precise identification, as well. Aim: To present our own experience in the isolation of Brucella species from blood cultures, by the Bact/Alert automated system, identification by the VITEK 2 compact system and antimicrobial susceptibility of isolated strains. Material and Methods: Patients from various regions of Macedonia hospitalized in the University Infectious Diseases and Febrile Condition Clinic in Skopje. FAN blood culture bottles (aerobic and anaerobic) of the Bact/Alert system were used, inoculated with 5–10 ml of blood, incubated under continuous agitation and monitored for up to 5 days or until they became positive (in our cases for 2–3 days). Confirmations of all isolates were made by the VITEK 2 automated system on GN cards. Results: During a period of three years, 113 blood cultures from patients with diagnosis of brucellosis hospitalized at the above-mentioned clinic were examined. A total of 16 blood cultures from different patients were positive (14.2%), showing Gram negative bacilli, oxidase positive small colonies on Columbia agar media. The isolates were identified as four biochemically different types of B. mellitensis, mainly within 8 hours. Susceptibility testing by the disk diffusion method on Muller Hinton agar showed sensitivity of all strains to cephalosporin, tetracycline, aminoglycoside and quinolone antibiotic groups. Conclusion: With the BacT/Alert system Brucella spp. were isolated in 14.2% of suspected cases of brucellosis. Isolation was done within 2–3 days. Only B. meliten- sis from the Brucella genus could be identified by the VITEK 2 system and some biochemical differences could be detected. The VITEK 2 system is not able to determine the susceptibility of B. melitensis. The Disk-diffusion method used in this study showed sensitivity to all tested antibiotics, although not recommended by CLSI for the Brucella genus.
Keywords: Brucella; BacT/Alert blood culture system; VITEK 2 compact system